A prospective study of hepatitis C incidence in Australian prisoners. (15th July 2014) - Luciani, Fabio; Bretaña, Neil Arvin; Teutsch, Suzy; Amin, Janaki; Topp, Libby; Dore, Gregory J.; Maher, Lisa; Dolan, Kate; Lloyd, Andrew R.; HITS‐p investigators
Abstract Aims To document the relationships between injecting drug use, imprisonment and hepatitis C virus (HCV) infection. Design Prospective cohort study. Setting Multiple prisons in New South Wales, Australia. Participants HCV seronegative prisoners with a life‐time history of injecting drug use (IDU) were enrolled and followed prospectively (n = 210) by interview and HCV antibody and RNA testing 6–12‐monthly for up to 4 years when in prison. Measurements HCV incidence was calculated using the person‐years method. Cox regression was used to identify predictors of incident infection using time‐dependent covariates. Results Almost half the cohort reported IDU during follow‐up (103 subjects; 49.1%) and 65 (31%) also reported sharing of the injecting apparatus. There were 38 HCV incident cases in 269.94 person‐years (py) of follow‐up with an estimated incidence of 14.08 per 100 py [confidence interval (CI) = 9.96–19.32]. Incident infection was associated independently with Indigenous background, injecting daily or more and injecting heroin. Three subjects were RNA‐positive and antibody‐negative at the incident time‐point, indicating early infection, which provided a second incidence estimate of 9.4%. Analysis of continuously incarcerated subjects (n = 114) followed over 126.73 py, identified 13 new HCV infections (10.26 per 100 py, CI = 5.46–17.54), one of which was an early infection case. Bleach‐cleansing of injecting equipment and opioid substitution treatment were not associated with a significant reduction in incidence. Conclusions In New South Wales, Australia, imprisonment is associated with high rates of hepatitis C virus transmission. More effective harm reduction interventions are needed to control HCV in prison settings.